2022
DOI: 10.1093/tropej/fmac056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concomitant Tuberculosis Infection on COVID-19 Disease in Children: A Matched, Retrospective Cohort Study

Abstract: Background Coronavirus disease 2019 (COVID-19) has had devastating effects on the health of millions globally. Patients with tuberculosis (TB) are a vulnerable population. There is paucity of data to assess association between the 2 diseases in Pediatric population. Objective To elucidate the effect of concomitant TB on clinical course of pediatric COVID-19 disease. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 16 publications
0
20
0
2
Order By: Relevance
“…Co-infection with SARS CoV-2 and MTB is of concern as the diagnosis of tuberculosis is more likely to be missed due to nonspecific presentation and a lack of typical radiological findings. Preexisting TB and underlying lung comorbidities aggravate the disease in COVID-19 (Tadolini et al, 2020) possibly through (Kumar et al, 2021), further a tertiary care hospital in India also showed association of TB (10%) in paediatric COVID-19 patients (Mathur et al, 2022).…”
Section: Covid-19 and Tuberculosis Coinfectionmentioning
confidence: 85%
“…Co-infection with SARS CoV-2 and MTB is of concern as the diagnosis of tuberculosis is more likely to be missed due to nonspecific presentation and a lack of typical radiological findings. Preexisting TB and underlying lung comorbidities aggravate the disease in COVID-19 (Tadolini et al, 2020) possibly through (Kumar et al, 2021), further a tertiary care hospital in India also showed association of TB (10%) in paediatric COVID-19 patients (Mathur et al, 2022).…”
Section: Covid-19 and Tuberculosis Coinfectionmentioning
confidence: 85%
“…As more data are revealed, pediatric TB has emerged to be a hidden threat behind the effects of COVID-19 as recent data showed how exposed pediatric patients are more susceptible to the disease than we previously thought [ 57 ], with signs of increased household transmissions from stay-at-home measures due to various risk factors such as tobacco smoking [ 6 ], as well as worse prognoses from co-infection [ 73 ], despite TB being a preventable and treatable disease. Ryckman et al in their review article on “Ending tuberculosis in a post-COVID-19 world” suggested that a person-centered, equity-oriented response focusing on targeting the widened health disparities as a result of the pandemic is key to our approach moving forward [ 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…These patients had a more severe disease course with lower SpO 2 on arrival, higher mechanical ventilation rates, longer length of hospital stays, and worse outcomes. Considering that TB is preventable and treatable, the conclusion of their study pointed out once again to the importance of screening, diagnosing, and treating for pediatric tuberculosis, especially during the pandemic to prevent worse outcomes with co-infection [ 73 ].…”
Section: Sars-cov-2 Co-infection In Childrenmentioning
confidence: 99%
“…In addition, in HIV-positive patients, who are several times more likely to develop pulmonary TB than those without HIV, physicians must exercise caution, because the use of highly active antiretroviral therapy in patients who are already infected with TB may result in paradoxical worsening of pulmonary disease [9]. During the multiple waves of the coronavirus disease 2019 (COVID-19) pandemic, numerous studies in adults revealed that patients with COVID-19 and TB have a two times greater risk of death than those without TB and are less likely to recover than patients with COVID-19 without TB [35]. Comorbidity with TB is strongly associated with moderate-severe COVID-19 illness in children at admission [35].…”
Section: Discussionmentioning
confidence: 99%
“…During the multiple waves of the coronavirus disease 2019 (COVID-19) pandemic, numerous studies in adults revealed that patients with COVID-19 and TB have a two times greater risk of death than those without TB and are less likely to recover than patients with COVID-19 without TB [35]. Comorbidity with TB is strongly associated with moderate-severe COVID-19 illness in children at admission [35]. Concomitant mucormycosis and TB infection is uncommon [36,37], and the outcomes of the ten cases documented in the literature have been poor [37].…”
Section: Discussionmentioning
confidence: 99%